1991
DOI: 10.1007/bf01665316
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic factors in primary gastrointestinal leiomyosarcoma: A retrospective study

Abstract: Thirty-six patients who were admitted for surgical resection of leiomyosarcomas of the gastrointestinal tract to the Department of Surgery II, Kanazawa University Hospital, Kanazawa, Japan and its affiliates are included in the study. Follow-up data on survival is available for 32 patients. The clinico-pharmacologic variables, such as tumor site, tumor size, cellularity, mitotic index, and DNA ploidy pattern were analyzed and the results proved to correlate with the prognosis. Thirteen (41%) of the patients pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
31
1

Year Published

1993
1993
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 13 publications
3
31
1
Order By: Relevance
“…This is the first time that the degree of malignancy was demonstrated by the number of the predictive parameters of malignancy. Previous studies have demonstrated that the adverse outcome of GISTs correlates with the increase in the tumor size, 12,16,25,[50][51][52][53] mitotic rate, 20,25,51,52,54 cellularity 51,52,55 and nuclear atypia. 16 In addition, tumor site 23,56,57 from the upper to lower GI tract seemingly had an effect on the outcome too.…”
Section: Discussionmentioning
confidence: 99%
“…This is the first time that the degree of malignancy was demonstrated by the number of the predictive parameters of malignancy. Previous studies have demonstrated that the adverse outcome of GISTs correlates with the increase in the tumor size, 12,16,25,[50][51][52][53] mitotic rate, 20,25,51,52,54 cellularity 51,52,55 and nuclear atypia. 16 In addition, tumor site 23,56,57 from the upper to lower GI tract seemingly had an effect on the outcome too.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, however, tumor size is internationally recognized as an independent and useful prognostic factor, for GISTs at least [37, 38, 39, 40, 41, 42]. In our study as well as others, the mutation-positive tumors were larger than the mutation-negative ones, so it needs to be determined whether not only tumor size but also mutations in exon 11 of the c-kit gene are independent and useful prognostic factors.…”
Section: Discussionmentioning
confidence: 75%
“…In our case, there was a GIST mass of the stomach showing extra gastric growth [5][6][7]. We reported on a unique and clinically and surgically significant case of GIST.…”
Section: Discussionmentioning
confidence: 94%
“…While there are studies about the severity of mesenchymal tumors by various criteria for malignancy, such as tumor size, cellularity, mitotic index, and DNA content [5], submucosal tumors of the stomach including GISTs have been classified into four growth patterns according to a previous report [6], namely, intragastric, intraluminal, extra gastric, and mixed patterns. In our case, there was a GIST mass of the stomach showing extra gastric growth [5][6][7].…”
Section: Discussionmentioning
confidence: 99%